Tasawuf sebagai Solusi Krisis Manusia Modern: Analisis Pemikiran Seyyed Hossein Nasr - Dedy Irawan (Tasfiyah: Jurnal Pemikiran Islam, 2019)
This article departs from the problems of spiritual crisis experienced by modern man today, it caused by the secularization as the core of the modernism, which stated religion as a private and was not a public matter. Syed Hossein Nasr is one of Muslim scholar who struggled to solve this matter, because he had witnessed the negative effect of the modernization. He also develop his idea about Islam Traditionalism based on Tasawuf. His works on Tasawwuf and his views are very relevant and very good for compiling and improving the moral decadence and spiritual emptiness that modern humans need today. Because he has accepted religion and even left him. Through literature studies with qualitative methods, this paper tries to explain about tasawwuf according to Syed Hossein Nasr, expected to provide benefits in an effort to improve morals and help modern humans from spiritual emptiness through Tasawwuf education.